Malih: An Ethnography Approach on Malioboro’s Social Change and Empowerment Discourse - Setyastama, R.; Soelistiyono, Anitiyo; Ahmed, Tanjeel; Larsari, Vahid Norouzi (Prosperity: Journal of Society and Empowerment, 2024)
This study investigates the liminal experiences of street vendors on Malioboro Street, Yogyakarta, and the street itself as dynamic entities shaped by governmental regulations and social realities. It explores the interplay between power, state governance, small and medium-sized economies, and socio-cultural phenomena, focusing on community empowerment. Employing ethnographic methods, the research provides an in-depth, qualitative understanding of the street vendors' lived experiences and the socio-economic environment of Malioboro. The findings reveal despite the government's pro-SME stance, restrictive urban policies frequently undermine the vendors' stability and economic security. This discord creates a persistent state of liminality for the street vendors, who are continuously displaced and rendered powerless to shape their lives. The study underscores the importance of inclusive and humane urban governance that balances regulatory objectives with the socio-economic realities of street vendors. It calls for involving vendors in policy development, creating flexible regulatory frameworks, and investing in supportive infrastructure. By fostering inclusive, participatory, and culturally rich urban environments, it is possible to create economically vibrant and socially equitable spaces, benefiting all city residents.